Experiment on seagrass (Zostera marina) response to chronically elevated temperature: pigments - Sawall, Yvonne; Pansch, Christian; Ito, Maysa (In: Sawall, Y et al. (2021): Experiment on seagrass (Zostera marina) response to chronically elevated temperature [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937394, 2021)
This study simulated a 9-months warming scenario on the common seagrass Zostera marina from winter into summer (December 2015 - August 2016) in the Western Baltic Sea (Kiel Fijord), using outdoor mesocosms. Two treatments were applied: Ambient temperature regime (Ambient) and Ambient + 3.6C (Heat) over the entire course of the experiment. Temperature regimes were compared to the 22-year temperature average in the area. This dataset shows monthly chlorophyll-a and beta-carotene concentration of one shoot per box. Unit is µg per mg of leaf dry weight. The organization of the data is hierarchical: Treatment (Heat, Ambient), Benthocosms number (6 benthocosms per treatment), Seagrass box number (4 boxes per benthocosm).
Keywords: flowering; Seagrass; Seasonality; Sea surface temperature rise; thermal tolerance; winter warming; Zostera marina